Integrating Australian Employment Law Practice in Support of People with Disabilities in Indonesia - Arpangi; Denny Suwondo; Andri Winjaya Laksana; Chami Yassine (UIN Sunan Gunung Djati, 2025)
Individuals with disabilities encounter markedly diminished work prospects relative to their non-disabled counterparts, attributable to societal hurdles, cultural bias, and inadequate legal safeguards. This study seeks to assess and incorporate inclusive employment practices from Australia into the legal and institutional framework of Indonesia. The research employs a normative legal method, incorporating doctrinal analysis and comparative study, to examine Australia's *Disability Employment Services (DES)* framework and the *Disability Discrimination Act 1992 (DDA)*, revised as of July 2023. The contrast underscores possible adaptations within Indonesia’s employment legislation framework, which remains deficient in explicit procedures for reasonable accommodation, efficient enforcement of disability employment quotas, and organized career coaching assistance. Furthermore, the study highlights significant disparities in institutional capability and legal culture between the two nations—Australia maintains a rights-based anti-discrimination legal framework, but Indonesia persists with sectoral and charity-focused methodologies. The results demonstrate that the partial integration of DES and DDA concepts is achievable, contingent upon contextual modifications to accommodate Indonesia's socio-political conditions, institutional constraints, and prevailing legal structures. Essential recommendations encompass the formulation of adaptable work accommodation regulations, the introduction of wage subsidies or tax incentives, the creation of training programs specific to disability categories, and the enhancement of employment oversight agencies equipped to combat workplace discrimination. These findings confirm that implementing Australia’s inclusive employment policies could strategically advance the establishment of a fairer and empowered workplace for individuals with disabilities in Indonesia, aligning with global standards and Indonesia’s constitutional commitment to equality.